Values of Kebhinekaan in Local Wisdom in The Digital Era: A Study of The Sesaji Ritual in Telaga Sarangan, Magetan, East Java - Rosidah, Feryani Umi; Putra, Prima Suhardi; Azisi, Ali Mursyid (Universitas Negeri Semarang, 2023)
An act of “Kebhinekaan” is the main basis foundation in the life of Indonesian society. Diversity is a gift that cannot be negated so need to be respected as well as acknowledged. This study analyzes ritual offerings phenomenon practiced by the local community around Telaga Sarangan, Magetan, and East Java in preserving “Kebhinekaan” in the digital era. Used qualitative approach as well as Clifford Gertz’s theory on religion and symbol, the article shows that the ritual offerings consisted of two sessions. The main ritual is a cultural carnival (carving and throwing a tumpeng). The second is a pre-ritual (Kambing Kendit slaughter, pilgrimage to the tombs (Kyai and Nyai Pasir), and thanksgiving. Morever, the ritual aims to thank of God's blessings and maintain safety and harmony. The article argues that rituals can be a medium in strengthening the values of “Kebhinekaan”and creativity through the carnival events. The events provide various values including religious and cultural meanings, strengthen kinship, humility, safety, and symbolic values (local wisdom). As a result, an act of “Kebhinekaan” and local wisdom strengthenes national identity and integrity through society's innovation and creativity of local community members.